Deliver Us from Evil - Baldacci, David; McLarty, Ron (New York Hachette Audio, 2010)
Shadowy operative Shaw and Reggie Campion, a woman working for a secret vigilante group, must work together in a deadly duel of nerve and wits against a surprising enemy, in a struggle that leads them around the world at a breakneck pace.
Unabridged.
Compact discs.
Read by Ron McLarty.
Keywords: International relations -- Fiction; Audiobooks; Spy stories; Suspense fiction